High-performance liquid chromatographic determination of 5-hydroxymethyl furfural in roasted plantain cultivars - Lasekan , Ola; Khatib, Alfi; Juhari, Hanisah; Patiram, Parveen; Lasekan, Seye (WFL Publisher, 2012)
The extent of Maillard reaction and the development of 5-(hydroxymethyl)-2-furaldehyde (HMF) were evaluated in two roasted plantain cultivars (French sombre and Dwarf kalapua), at different ripening stages. Roasting at high temperature (210°C) and roasting duration were shown to increase the development of HMF in the roasted samples. Similarly, ripening stage had significant influence on the development of HMF. The colour and fluorescence intensities were significantly (P > 0.05) increased by the roasting conditions and the degree of ripening. In addition, the plantain cultivars showed positive correlations with HMF, fluorescence, colour index and the sugars, respectively.